1995
DOI: 10.1093/oxfordjournals.humrep.a136332
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and preventing inherited disease: Nucleated erythrocytes in maternal blood: quantity and quality of fetal cells in enriched populations

Abstract: The discovery of nucleated erythrocytes in maternal circulation provides a potential source for non-invasive prenatal diagnosis. We have evaluated the use of a three-stage procedure to determine the number of cells that are of fetal rather than maternal origin. First, monoclonal antibodies specific for CD45 and CD14 were used in conjunction with a magnetic (MACS) column to deplete unwanted leukocytes from maternal blood. This was followed by a positive MACS enrichment for nucleated erythrocytes, using an anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hence, considerable efforts were made from the 1980s to early 2000s to find adequate, general markers for specific fnRBC selection. The surface marker CD71 (transferrin receptor) combined with CD36 and/or glycophorin A (GPA) are the most widely used targets, 48,[58][59][60] and Bianchi and colleagues showed that adding anti-GPA antibodies to anti-CD71 or anti-CD36 substantially improves fnRBC selection and accuracy of fetal sex prediction. 61,62 Choolani et al confirmed that primitive erythroblasts were the predominant cell type up to 12 weeks gestation, declining rapidly thereafter.…”
Section: Fetal Nucleated Red Blood Cellsmentioning
confidence: 99%
“…Hence, considerable efforts were made from the 1980s to early 2000s to find adequate, general markers for specific fnRBC selection. The surface marker CD71 (transferrin receptor) combined with CD36 and/or glycophorin A (GPA) are the most widely used targets, 48,[58][59][60] and Bianchi and colleagues showed that adding anti-GPA antibodies to anti-CD71 or anti-CD36 substantially improves fnRBC selection and accuracy of fetal sex prediction. 61,62 Choolani et al confirmed that primitive erythroblasts were the predominant cell type up to 12 weeks gestation, declining rapidly thereafter.…”
Section: Fetal Nucleated Red Blood Cellsmentioning
confidence: 99%